Pemasaran Berbasis Komunitas dan Kemitraan Pada Kaliboto Green Institute - sulistyo (Surakarta Abdimas Journal, 2024)
Abstract This study aims to identify and analyze community-based marketing strategies and partnerships undertaken by Kaliboto Green Institute, an institution engaged in goat farming, fish farming, and fermented animal feed processing in Central Java. Using a qualitative approach through case studies, this research explores the role of local communities and strategic partnerships in expanding markets and increasing product sales. Data were obtained through in-depth interviews, direct observation, and document analysis. The results show that community-based marketing is effective in strengthening local community involvement and increasing product acceptance in the market. Partnerships with cooperatives and educational institutions also contributed significantly in supporting product marketing and distribution. However, some challenges such as coordination among partners and limited resources need to be addressed to improve the success of the program. This study provides practical guidance for small and medium-sized enterprises to leverage the power of community and partnerships in marketing strategies. In addition, the findings also have implications for the development of sustainable marketing policies in the livestock and fisheries sectors. Keywords: Community-Based Marketing, Partnership, Livestock